Clinical models of cardiovascular regulation after weightlessness - Robertson, D; Jacob, G; Ertl, A; Shannon, J; Mosqueda-Garcia, R; Robertson, R M; Biaggioni, I (Medicine and science in sports and exercise, 1996)
After several days in microgravity, return to earth is attended by alterations in cardiovascular function. The mechanisms underlying these effects are inadequately understood. Three clinical disorders of autonomic function represent possible models of this abnormal cardiovascular function after spaceflight. They are pure autonomic failure, baroreflex failure, and orthostatic intolerance. In pure autonomic failure, virtually complete loss of sympathetic and parasympathetic function occurs along with profound and immediate orthostatic hypotension. In baroreflex failure, various degrees of debuffering of blood pressure occur. In acute and complete baroreflex failure, there is usually severe hypertension and tachycardia, while with less complete and more chronic baroreflex impairment, orthostatic abnormalities may be more apparent. In orthostatic intolerance, blood pressure fall is minor, but orthostatic symptoms are prominent and tachycardia frequently occurs. Only careful autonomic studies of human subjects in the microgravity environment will permit us to determine which of these models most closely reflects the pathophysiology brought on by a period of time in the microgravity environment.